2014
DOI: 10.1002/macp.201400345
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Polyethylenimine‐Modified Biodegradable Complex Micelles as Gene Transfer Vector for Proliferation of Endothelial Cells

Abstract: Polyethylenimine (PEI) can perfectly condense with DNA and sufficiently transfer genes, but its high toxicity limits its application. Here, complex micelles are prepared as low‐toxicity gene vectors by self‐assembly of two block copolymers in aqueous solution. The complex micelles consist of a biodegradable poly(lactide‐co‐glycolide) (PLGA) core and a mixed poly(ethylene glycol) (PEG)/PEI shell. The ZNF580 gene plasmid (pEGFP‐ZNF580), which has the ability of enhancing the proliferation of vascular endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 53 publications
0
55
0
Order By: Relevance
“…30 However, the drawbacks of high-molecular weight PEI, including nondegradability and high cytotoxicity, limit its application in vivo. [31][32][33] In recent decades, the excellent properties of star-shaped polymers have attracted researchers' attention. Compared with linear counterparts, star-shaped polymers with the same molecular weight have showed higher transfection efficiency.…”
Section: Feng Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…30 However, the drawbacks of high-molecular weight PEI, including nondegradability and high cytotoxicity, limit its application in vivo. [31][32][33] In recent decades, the excellent properties of star-shaped polymers have attracted researchers' attention. Compared with linear counterparts, star-shaped polymers with the same molecular weight have showed higher transfection efficiency.…”
Section: Feng Et Almentioning
confidence: 99%
“…27,31 Briefly, 0.03 g of D-sorbitol, 4.50 g of LA and 0.50 g of MMD were added into the Schlenk full of nitrogen. Then, the Schlenk was immersed in an oil bath at 125°C for 24 h. The copolymer was purified and dried at room temperature in vacuum for 24 h. The yield was 79.4%.…”
Section: Synthesis Of P(mmd-co-la)-g-pei Cationic Copolymermentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18] For example, Lv et al reported that a complex micelle consisting of a biodegradable PLGA core and a mixed PEG/PEI shell can be prepared via the self-assembly of two block copolymers (PEG-b-PLGA and PLGA-b-PEI) in aqueous solution. This micelle can be used as a gene carrier for enhancing proliferation of endothelial cells.…”
mentioning
confidence: 99%
“…This micelle can be used as a gene carrier for enhancing proliferation of endothelial cells. 17 Recently, Li et al developed a new kind of gene carrier based on the amphiphilic block copolymers containing biodegradable hydrophobic depsipeptide copolymers and branched PEI. 18 We have also developed a novel type of PEI-based amphiphilic core-shell nanoparticles (NPs) with diameters in the range of 100-300 nm and explored their potential application as nanocarriers for drug and gene deliveries.…”
mentioning
confidence: 99%